Solve the linear system of equations.

x - 3y = -6

5x + 3y = 42

hello

multiply first equation with 5,

(x - 3y = -6) *5

5x-15y = -30

subtract this equation from second equation( 5x + 3y = 42)

5x + 3y = 42 -

18 y = 72

y = 4

substitute y = 4 in (x - 3y = -6

x - 3*4 = -6

x= 6

ANSWER IS

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up